PENINGKATAN KOMPETENSI PEMBUATAN UAV SISWA SMK ANGKASA 1 JAKARTA MELALUI PELATIHAN TEKNOLOGI DIRGANTARA - Widanto, Muhammad Hadi; Warsiyanto, Budi Aji; Agustianingsih, Riskha; Fairuza, Syarifah; Sari, Rafika Arum; Jayadi, Muhamad (Universitas Islam 45 Bekasi, 2025)
The development of Unmanned Aerial Vehicle (UAV) technology has advanced rapidly and is now applied in agriculture, mining, forestry, and the creative industry. Indonesia, with its vast territory and diverse topography, has great potential for UAV utilization. However, mastery of this technology at the vocational school level remains limited. SMK Angkasa 1 Jakarta, particularly in its aviation department, faces this challenge and requires strengthened competencies in UAVs. In response, Universitas Dirgantara Marsekal Suryadarma carried out a Community Service program as a form of technology and innovation transfer. The program aimed to enhance students’ conceptual understanding and basic skills related to UAVs, introduce prototype design processes, familiarize them with UAV system components, and provide learning modules and equipment for independent learning. The methods included the preparation of teaching modules, delivery of UAV materials (theory, conceptual design, electrical and navigation systems), hands-on practice in building polyfoam UAV prototypes, interactive discussions, and evaluations through pre-tests, post-tests, and questionnaires. The results showed a significant improvement in students’ knowledge, indicated by the increase in post-test scores and positive feedback on the training. The provision of UAV prototypes and modules further strengthened practice-based learning at the school. In conclusion, the training successfully improved students’ competencies while contributing to the quality of vocational education in aviation. Recommendations include establishing a UAV laboratory, continuous teacher training, broader collaboration with industry, and promoting student work through UAV competitions and exhibitions.